(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Local governance serves as the first line of defense in managing crises such as natural disasters, pandemics, and industrial emergencies. This study adopts a mixed methods approach, comb ining secondary data analysis with primary data from surveys and interviews, to evaluate preparedness, coordination, and recovery effectiveness across three representative case studies. Comparative analysis using a SWOC framework revealed that proactive le adership, community engagement, and inter agency collaboration were key strengths, while weaknesses included resource shortages and limited infrastructure. Opportunities for improvement lie in capacity building and digitalization of crisis management, whil e persistent challenges include unpredictable environmental and social factors. The findings underscore the necessity of localized, adaptive, and inclusive governance strategies to enhance resilience and ensure effective crisis response.